The Sixth Sense that Gives Burdens: Narratives and Explanations on the ‘Gifted People’s Encounters with the Supernatural - Ratna Andriani Fabrian (Antropologi Indonesia, 2020)
In Jakarta, stories of people experiencing ghosts were not uncommon or peculiar. For some people, a given sixth sense allows them to gain advantages by communicating with the supernatural—this is considered as a gift. But, this ‘gift’ carries a side-effect, that is, the bearers may often get disturbed by ghosts due to their own supernatural sensitivity. To protect themself from supernatural disturbances, the bearers have to refrain from committing certain actions and have to constantly and solemnly pray. However, if they find the disturbances unbearable, they may visit a spiritual healer who has more power in controlling the supernatural. This paper aims to highlight the narratives on ghostly encounters and disturbances of people with a sixth sense. The featured narratives were of four people with a sixth sense from different backgrounds and statuses. They all lived in Jakarta. It focuses on their life histories as well as their beliefs on the supernatural. Despite their different personal histories, all informants conveyed that they have endured significant painful experiences before becoming susceptible to ghostly disturbances. It was then evident that their intriguing ghostly encounters were one of the results of their distressing past events. However, cultural beliefs denied and/or concealed the underlying issue and regarded it as a mere supernatural phenomenon. This raises a question on the conceptualization of mental health problems and its categorization cross-culturally; should a cultural symptom be classified as a mental health problem?